2002
DOI: 10.1046/j.1365-2567.2002.01524.x
|View full text |Cite
|
Sign up to set email alerts
|

Opposing roles of activator protein‐1 and CCAAT/enhancer binding protein β in the regulation of inducible granulysin gene expression in a human monocytic cell line, THP‐1

Abstract: SUMMARYWe previously reported that inducible granulysin gene expression in a human monocytic cell line, THP-1 is dominantly dependent on transcription factor activator protein-1 (AP-1). Here, we further examined the precise regulatory mechanisms underlying granulysin gene expression using THP-1 cells treated with Acholeplasma laidlawii. Transfection of reporter gene constructs into THP-1 cells indicated that the presence of a positive regulatory element(s) is located from À329 to À85 base pairs, containing two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…In addition, it has been reported that activation of AP-1 is regulated via MAPK signaling pathways (11). Thus, we could not exclude the participation of AP-1 in M. bovis BCG-induced LL-37 expression in A549 cells.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, it has been reported that activation of AP-1 is regulated via MAPK signaling pathways (11). Thus, we could not exclude the participation of AP-1 in M. bovis BCG-induced LL-37 expression in A549 cells.…”
Section: Discussionmentioning
confidence: 80%
“…Although the C/EBP molecules other than C/EBP␤ can also bind to the C/EBP binding site, C/EBP␤ is especially involved in the inducible expression of several genes that are important for inflammatory and immune responses (31,32,49,50). Therefore, to identify the C/EBP␤ protein, the nuclear extract from the stimulated EBC-1 cells was preincubated with C/EBP␤-specific antibody before the addition of a radiolabeled probe.…”
Section: Vol 75 2007 Par-2-mediated Inflammatory Responses By Serramentioning
confidence: 99%
“…[14][15][16][17] Consequently both forms of GNLY can be induced in the course of inflammation and have also been shown to be up-regulated by stimulation of lymphoid cells by proinflammatory mediators and pathogenassociated molecular patterns. 18,19 GNLY exhibits lytic activity against a variety of microorganisms and tumors. 3,14,[20][21][22] It binds to a variety of lipids, including cholesterol and sphingolipids, and damages microbial cell membranes by binding to negatively charged molecules.…”
Section: Introductionmentioning
confidence: 99%